Ionization of P Atom, P\(_2\) and PX (X = H, C, N, O) Molecules by Electron Impact: Theoretical Studies (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
Being a biogenic element atomic Phosphorus is one of the significant constituents of the universe [1]. Gulick [2] found a pivotal role of phosphorus in the origin of life. The phosphoruscontaining molecules like PH, PC and PN radicals, have been observed in interstellar gas clouds [3–5] and they are proposed to be present under appropriate conditions. Phosphorous hydrides having numerous applications, are detected in cool stellar atmosphere [6] and circumstellar envelopes. Thus, the present paper addresses the electron impact processes of atomic phosphorus and its diatomic compounds. Ground and metastable states of Atomic P give rise to the probability of presence of metastable state in the atomic beam used for cross section measurement [7]. We have employed the well-known Spherical Complex Optical Potential (SCOP) formalism to calculate total inelastic cross sections. The semi-empirical CSP-ic method is used to extract total ionization cross section \(Q_{ion}\) from total inelastic cross section [8]. A variant CSP-ic approach is also attempted for these targets.
Keywords: Phosphorus; Electron impact ionization; Complex potential